Acute arsenic poisoning: absence of polyneuropathy after treatment with 2, 3-dimercaptopropanesulphonate (DMPS). Issue 9 (September 1994) - Moore, D F; O'Callaghan, C A; Berlyne, G; Ogg, C S; Davies, H A; House, I M; Henry, J A
Abstract : Two men aged 19 and 21 years ingested 1 g and 4 g respectively from 3 kg of a white crystalline powder that they thought was a substance of abuse. It was later identified as almost pure arsenic trioxide. Both had nausea and vomiting and one developed acute renal failure. Each was treated with 2, 3-dimercaptopropanesulphonate (DMPS), and made a full recovery with no evidence of prolonged renal or neurological impairment. The DMPS-arsenic complex is probably associated with lower penetration into the CNS and as a consequence treatment with DMPS may result in lower acute and chronic neurotoxicity than treatment with the currently standard recommended chelating agent dimercaprol (British Anti-Lewisite; BAL).